Extremely loud & incredibly close [videorecording (DVD)] - Daldry, Stephen; Hanks, Tom; Bullock, Sandra; Horn, Thomas, 1997-; Davis, Viola, 1965-; Goodman, John, 1952-; Wright, Jeffrey. (Jeffrey Charles), 1965-; Sydow, Max von, 1929-2020-; Foer, Jonathan Safran, 1977- (Distributed by Warner Home Video, 2012)
Oskar is convinced that his father, who died in the 9/11 attacks on the World Trade Center, has left a message for him hidden in the city. Feeling disconnected from his grieving mother and driven by an active mind that refuses to believe in things that can't be observed, Oskar begins searching New York City for the lock that fits a mysterious key he found in his father's closet. His journey through the five boroughs takes him beyond his loss to a greater understanding of the world around him.